Australia's sporting success : the inside story - Bloomfield, J. (John), 1932- (UNSW Press, 2003)
"John Bloomfield traces the development of Australian sport from the early nineteenth century, when qualities of nationalism, social cohesion and tenacity developed as distinctive Australian character traits, partly as a result of sport. However this book's primary focus is on the modern era and a nation's investment in science, management, coaching and junior sport. The Australian sports system has become a blueprint for success, and is now being copied around the world."--Jacket